How interculturally competent am I? : an introductory thesis writing course for international students - Houghton, Stephanie Ann (Cambridge Scholars Publishing, 2013)
This textbook aims to help students to develop thesis-writing skills through experiential learning by conducting a research project based on a diary study, and reporting on it in a mini-thesis. It was developed for the benefit of international students who, in their penultimate year of undergraduate study, are planning to write a graduation thesis in English related to intercultural communication in their final year with little or no prior knowledge of the subject, or of thesis-writing itself ...